2005
DOI: 10.1021/jo052157l
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cyclopropanation of 1-Alkynylphosphonates by Cp2ZrCl2/2EtMgBr/2AlCl3 To Afford Cyclopropylmethylphosphonates

Abstract: [reaction: see text] The reagent system Cp2ZrCl2/2EtMgBr/2AlCl3 converts 1-alkynylphosphonates into cyclopropylmethylphosphonates 3 in good isolated yields. Ethers, chlorides, and other cyclopropyl groups are compatible with the reaction conditions. Deuterium labeling is consistent with the formation of stable cyclopropylmethylbimetallic phosphonates by ring contraction of the corresponding aluminacyclopentenylphosphonate. Temperature is crucial; apparently, the cyclopropylmethylbimetallic phosphonates are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…According to the work of Srebnik characteristic chemical shifts for alkenyl phosphonates are usually observed at about δ ϭ 20 ppm in the 31 P NMR spectrum. [9] This corresponds well to the value of δ ϭ 24.40 ppm observed for 5. Also, the 13 C NMR signals at δ ϭ 205.96 and 205.97 ppm coming from the carbonyl groups at C-12/C-12* as well as the signals at δ ϭ 40.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…According to the work of Srebnik characteristic chemical shifts for alkenyl phosphonates are usually observed at about δ ϭ 20 ppm in the 31 P NMR spectrum. [9] This corresponds well to the value of δ ϭ 24.40 ppm observed for 5. Also, the 13 C NMR signals at δ ϭ 205.96 and 205.97 ppm coming from the carbonyl groups at C-12/C-12* as well as the signals at δ ϭ 40.…”
Section: Resultssupporting
confidence: 85%
“…In the 31 P NMR spectrum we observed a single, incidentally isochronic signal at δ ϭ 21.38 ppm which again corresponds to the expected value for alkenyl phosphonates of about δ ϭ 20 ppm. [9] Also, the chemical shifts of the 13 C NMR signals for C-11/C-11* and C-12/C-12* again support the formation of the open-chain compound. Interestingly, the chloro substituent seems to have a fixing influence on the conformation of one of the two isomers concerning the free rotation of the phosphorus substituent.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…[1][2][3] Phosphonates and aminophosphonates have been found to possess chelating properties toward metals, 4 irreversible inhibition properties against serine proteases 5 and the ability to inhibit zinc-dependent enzymes of the metalloprotease family. [6][7][8] As part of ongoing research in our laboratory, we have reported different synthetic methods for the synthesis of novel, highly substituted vinyl phosphonate compounds from 1-alkynylphosphonates using zirconium(II) or titanium(II) reagents, [9][10][11][12][13][14][15][16][17][18][19][20] as well as the synthesis of fusedcyclopentenone phosphonates from 1-alkynylphosphonates via an intramolecular Pauson-Khand reaction 21 using molybdenum hexacarbonyl [Mo(CO) 6 ]. 22 In the course of our research on fused-cyclopentenone phosphonate compounds, 21 we encountered double bond migration.…”
mentioning
confidence: 99%
“…9 Recently, the reagent system Cp 2 ZrCl 2 /2 EtMgBr/2 AlCl 3 was shown to convert alk-1-ynylphosphonates into cyclopropylmethylphosphonates in good isolated yields. 10 As a consequence considerable effort has been directed towards the development of methods for their simple and effective preparation. 6 Recently, we have demonstrated that Knoevenagel condensation of (diethoxyphosphoryl)acetic acid with various aromatic aldehydes gives access to a range of (E)-3aryl-2-(diethoxyphosphoryl)acrylic acids 1.…”
mentioning
confidence: 99%